1988
DOI: 10.1021/ac00158a017
|View full text |Cite
|
Sign up to set email alerts
|

Total reflection energy-dispersive x-ray fluorescence spectrometry using monochromatic synchrotron radiation. Application to selenium in blood serum

Abstract: Monochromatic synchrotron X-radiation at The National Synchrotron Light Source (NSLS) has been Investigated as an excitation source for the direct energy-dispersion X-ray fluorescence (EDXRF) spectrometrlc analysis of metals In solution at parts per billion (ppb) levels In the total reflection geometry. A minimum detection limit (mdl) of 8 ppb was determined for selenium In human blood serum and In ; reposed NBS-SRM 1598 bovine serum. The results show that this method Is sufficiently sensitive for analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The first SR experiments were published in 1986 by Iida et al [14] followed by results of several other authors [15][16][17]. A recent review on SR-TXRF analysis was given by Streli et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…The first SR experiments were published in 1986 by Iida et al [14] followed by results of several other authors [15][16][17]. A recent review on SR-TXRF analysis was given by Streli et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…Maximal signal to noise ratio can be realized if the uorescence signal is measured in a position, where the contribution of anisotropic scattered radiation is minimal. [5][6][7][8][9][10] In the literature, several attempts have been made earlier that report signicant reduction of the spectral background and hence improved detection sensitivities of the XRF technique. Embong et al 11 have reported sub-ppm level detection sensitivities using a three-dimensional polarization excitation geometry for multi-element sediment samples by means of variation of various experimental parameters like excitation geometry, X-ray energy, secondary targets, operating voltage and current of the X-ray tube source, and thickness of lters installed in the spectrometer.…”
Section: Introductionmentioning
confidence: 99%